The Archaeological Survey of Alberta - William J. Byrne (1976)
With the passage of the Alberta Heritage Act 1973, the province of Alberta changed from a province with little or no legislation relevant to archaeological resource management to one with a modern integrated legislative package concerned not only with archaeological protection but also with the promotion of archaeological investigation and documentation. This legislation has, in the intervening two years, been supplemented by amendments to the original Act which have served to strengthen its authority, and by the establishment of a provincial agency designed specifically to implement the provisions of the Act as they pertain to archaeology. At this time it is possible to review the activities of the Survey in its first two years, and to predict future activities and developments.